Über ähnliche Aufsatzdreiecke einer Strecke - Giering, Oswald (Teaching Mathematics and Computer Science, 2007)
In this article we investigate (with methods of school geometry) a figure (PQ,ABC) consisting of three given similar triangles PQA, PQB, PQC with side PQ in common (Figure 1). We combine other triangles with this figure such as triangle ABC which is proved to be similar to the given triangles. The incircles of three additional triangles adjacent to triangle ABC will be determined.